Practices of Poverty Measurement and Poverty Profile of Nepal - Devendra Chhetry (Asian Development Bank (ADB), 2004)
This paper reviews the poverty measuring practices, available measures of poverty, and economic growth figures of Nepal. The currently available three poverty rates for fiscal years 1976/77, 1984/85, and 1995/96 are found to be not comparable mainly due to change in methodology over time. Despite such methodological changes, the three poverty rates average around 40 percent. Nepal has experienced relatively high economic growth during the Seventh (1985/86 to 1989/90) and the Eighth (1992/93 to 1996/97) Plan periods with no strong evidences of poverty reduction. This incompatible result is partially explained by comparing growth of the agricultural sector with the role of the sector in providing employment and income generation at the household level, and by comparing social indicators particularly literacy rate with the growth of the nonagricultural sector. Large discrepancies have been observed between the microeconomic (per capita household income/consumption) and macroeconomic (per capita GDP/private consumption) indicators, suggesting weak linkages between macro and micro economic development.
hdl:11540/1912
Keywords: 330; Armut; Armutsbekämpfung; Wirtschaftswachstum; Messung; Nepal